Particle Swarm Optimization Performance: Comparison Of Dynamic Economic Dispatch With Dantzig-Wolfe Decomposition - Ab Ghani, Mohd Ruddin; Hussein, Saif Tahseen; Jano, Zanariah; Tole, Sutikno (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2016)
-